Risk of neurologic or immune-mediated adverse events after COVID-19 diagnosis in the United States - Shelby S. Fisher; Arnstein Lindaas; Stella G. Muthuri; Patricia C. Lloyd; Joann F. Gruber; Morgan M. Richey; Hai Lyu; Angela S. Cheng; Lisa S. Kowarski; Mollie M. McKillop; Christine Bui; Tainya C. Clarke; et al. (PLoS ONE, 2025)
Introduction Neurologic or immune-mediated conditions have been evaluated as potential adverse events (AEs) in coronavirus disease 2019 (COVID-19) vaccine safety surveillance. To contextualize United States (US) surveillance findings, it is important to quantify the association of AEs with COVID-19 diagnoses among US adults before the introduction of COVID-19 vaccines. Methods Cohort and self-controlled risk interval (SCRI) designs were used in 2 US administrative claims data sources—Merative™ MarketScan ® Commercial Database (ages 18−64 years) and Medicare fee-for-service data (ages ≥ 65 years). AEs included Guillain-Barré syndrome (GBS), Bell’s palsy, encephalitis/encephalomyelitis, narcolepsy, immune thrombocytopenia (ITP), and transverse myelitis. The cohort (study period, 1 April 2020−10 December 2020) included adults with COVID-19 diagnoses and matched comparators. Inverse probability of treatment-weighted hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated. The SCRI (study period, 1 June 2020−10 December 2020) identified the AEs in risk windows after COVID-19 diagnosis and pre- and postexposure reference windows. Relative incidences (RIs) and 95% CIs were estimated with seasonality-adjusted conditional Poisson regression models accounting for outcome-dependent observation windows. Results The study observed a consistent association between COVID-19 diagnosis and GBS: MarketScan HR = 9.57 (95% CI, 1.23–74.74), RI = 8.53 (95% CI, 2.45–29.7); Medicare HR = 1.97 (95% CI, 1.04–3.74), RI = 4.63 (95% CI, 1.78–12.01). For ITP, the association was weaker, but still consistently elevated: MarketScan HR = 2.06 (95% CI, 1.20–3.53), RI = 1.74 (95% CI, 1.01–3.00); Medicare HR = 1.36 (95% CI, 1.18–1.57), RI = 1.91 (95% CI, 1.60–2.28). For all remaining AEs, there was not consistent evidence of an association with COVID-19, with estimates that were generally modest, imprecise, or varying by study design. Conclusions COVID-19 diagnoses were associated with an increased risk of GBS and ITP in both data sources and study designs. Increased risks of other neurologic/immune-mediated AEs cannot be ruled out.